Manejo integrado de mancha de hierro (Cercospora coffeicola (Berk y cooke)), en el cultivo de café (Coffea arabica) en Ecuador - Toalombo Huacon, Andrés Renan (2023)
Iron spot disease is caused by the fungus C. coffeicola, it is considered a disease of economic importance that affects the coffee crop, which causes damage to the plant at various stages, from the nursery to the established plantations; the most serious damage occurs in the fruit, but also affects leaves and branches. The information obtained was carried out through the technique of analysis, synthesis and summary, with the sole objective of establishing specific information in correspondence to the project, which has as its theme "Integrated management of iron spot (C. coffeicola), in the cultivation of coffee (C. arabica) in Ecuador". Based on the above, it was determined that, in some regions of Ecuador, the disease has affected almost 50 % of the coffee growing area, causing a yield loss of around 15 %, given that C. coffeicola thrives in a constantly warm and humid environment. Symptoms on leaves are round or oval spots with a size of 6 to 13 mm in diameter that start with yellow spots visible on the edges of the leaves and grow in a circular pattern as the disease progresses; these spots are black when young, but when the fruits of the fungus fall. Symptoms on branches occur on the soft parts, gray spots appear and extend several centimeters, sometimes covering the entire internode; the spots darken, the gray false bark cracks and the trunk is exposed. Lesions on fruit are round, sunken and of various sizes; infested cherries initially appear as small red or brown spots that enlarge and sink into the tissue, and the lesions are brown and sometimes surrounded by a purplish halo. It is important to establish vigorous coffee trees with a good root system and adequate shade; it is recommended that coffee trees be pruned as necessary to improve ventilation and reduce environmental humidity. As a general control measure for iron spot disease, it is important to avoid nutritional deficiencies and imbalances, since nutrition has a great influence on the development of the disease.